Amniotic fluid embolism as a cause of maternal mortality in China between 1996 and 2013: a population-based retrospective study - Mu, Yi (BMC Pregnancy Childbirth, 2016)
BACKGROUND: To analyse the maternal mortality ratio, demographic and pregnancy related details in women who suffered a fatal amniotic fluid embolism (AFE) in China. METHODS: A retrospective population based study using data collected as part of the National Maternal Mortality Surveillance System between 1996 and 2013. Data were collected onto a standardised form from women whose cause of death was listed as being secondary to AFE. RESULTS: Records were available for 640 deaths. Over the 17 year period the maternal mortality ratio for AFE decreased from 4.4 per 100,000 births (95 % confidence interval (CI):2.72–6.12) to 1.9 per 100,000 births (95 % CI:1.35–2.54). Over the same period the proportion of maternal deaths secondary to AFE increased from 6.8 to 12.5 %. The mean age of women who died was 30.1 years and the onset of the AFE occurred prior to delivery in 39 %. The most prominent presenting features included premonitory symptoms (29 %), acute fetal compromise (28 %), maternal haemorrhage (16 %) and shortness of breath (15 %). CONCLUSIONS: Maternal mortality secondary to AFE has decreased in China, however at a slower rate than mortality secondary to other conditions. Active surveillance is recommended to assess case fatality rates, risk factors and other lessons specific to this population.